DAMPAK COVID-19 TERHADAP PERUBAHAN HARGA SAHAM DAN VOLUME TRANSAKSI (STUDI KASUS PADA PT. BANK MANDIRI.Tbk) - Meiske Wenno (Soso-Q : Jurnal Manajemen, 2020)
The first case of the covid-19 in Indonesia was announced on March 2nd 2020. This research aims to find out the significant difference between stock prices and transaction volume at PT. Bank Mandiri, Tbk due to covid-19 pandemic. These data have been taken for 31 days before and 31 days after the first announcement of covid-19 corona virus in Indonesia. The data have been processed by paired sample ttest using SPSS version 26. The data processing results showed that there is a significant difference stock price of PT. Bank Mandiri, Tbk. between before and after the first announcement of the covid-19 case in Indonesia. This is indicated by the significance value of 0.00 < 0.05, which the stock price has decreased compared to before the covid-19 case. As for the volume transaction also showed difference significant, which the significance value is 0.01 < 0.05. The transaction volume after the announcement of shares shows an increasing value. Keywords: Stock Prices, Transaction Volume, Covid 19